GWAS identifies novel loci linked to seedling growth traits in highly diverse barley population under drought stress - Abdelfattah Badr; Hanaa H. El-Shazly; Mayada Mahdy; Matías Schierenbeck; Radwa Y Helmi; Andreas Börner; Helmy M Youssef (Scientific Reports)
Abstract Climate changes refer to long-term shifts in temperature and weather patterns that may cause drought, one of the major stresses hindering seed germination, plant growth, and crop productivity. Barley (Hordeum vulgare L) is considered one of the most drought-stress-tolerant cereals and may be used for elucidating genes for drought tolerance at seed germination and seedling stages that would pave the way toward improving the performance of all cereals. The current study was performed at IPK-Gatersleben (Germany) in 2023. Our aim was to explore the genetic basis of germination and seedling traits under drought stress (20% PEG6000 treatment) in a 198 global spring barley collection genotyped with 38,632 SNPs via Genotyping by Sequencing (GBS). The drought treatment significantly reduced the seed germination parameters and seedling traits in the genotypes of a global barley collection. Drought tolerance indices (DTI) for the measured germination and seedling traits indicate delayed and lower germination speed under drought stress than the control. The shoot fresh weight was the most affected trait, with a DTI of 37.4, followed by the seedling fresh weight SDLFW (DTI = 46.3) and root fresh weight (DTI = 47). In contrast, the root length DTI was the least affected trait by drought (78.2), followed by RDW DTI (72.8). GWAS was conducted using single-locus (CMLM) and multi-locus models (MLMM, Farm-CPU, BLINK), with significant marker-trait associations determined at -log10 (1.29E-06) ≥ 5.88. In our present study, we identified 79 highly significant SNPs distributed across the seven barley chromosomes related to the germination and seedling growth parameters under both control and drought conditions. Gene annotation of these highly significant SNPs revealed that 35 SNPs were in the exonic regions of genes that play roles in important plant biological and physiological processes. Further analysis exhibited 35 high-confidence candidate genes influencing barley germination and seedling growth under control and drought conditions. These genes represent promising targets for breeding and genetic enhancement efforts to improve drought tolerance in barley, potentially extending these benefits to other cereal crops.